2021
DOI: 10.1001/jamanetworkopen.2021.5697
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative In-Hospital Morbidity and Mortality of Patients With COVID-19 Infection Compared With Patients Without COVID-19 Infection

Abstract: This cohort study uses the Vizient Clinical Data Base to compare the postoperative in-hospital morbidity and mortality of surgical patients with COVID-19 infection with patients without COVID-19 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 7 publications
0
40
0
1
Order By: Relevance
“…Comparison of outcomes between acyanotic and cyanotic lesions was also performed. Demographics, LOS, rate of the presence of complications listed in the Vizient Clinical Data Base [ 6 ], in-hospital mortality, and total hospital costs were collected. To determine if there was a difference in admission severity of illness or mortality risk between the groups, queries were preformed from Vizient-defined “Acuity Scale Mortality” (severity of illness at admission) and “Relative Expected Mortality” (mortality risk at admission).…”
Section: Methodsmentioning
confidence: 99%
“…Comparison of outcomes between acyanotic and cyanotic lesions was also performed. Demographics, LOS, rate of the presence of complications listed in the Vizient Clinical Data Base [ 6 ], in-hospital mortality, and total hospital costs were collected. To determine if there was a difference in admission severity of illness or mortality risk between the groups, queries were preformed from Vizient-defined “Acuity Scale Mortality” (severity of illness at admission) and “Relative Expected Mortality” (mortality risk at admission).…”
Section: Methodsmentioning
confidence: 99%
“…2,5 Several studies have reported the perioperative outcome of SARS-CoV-2-infected patients. 6,7 A recent study found that surgical mortality was 23.8% in patients infected with COVID-19, and more than half of patients developed postoperative pulmonary complications. 6 In a similar study, mortality in surgical patients was shown to be two times higher in COVID-19-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with confirmed COVID-19 requiring surgery, it should be deferred due to the high risk of postoperative complications and nosocomial spread. 9 11 , 19 In our institutional protocol, all patients with COVID-19 symptoms (detected from the questionnaire) or with positive RT-PCR test results will have their surgery deferred by the doctor, and a clinical evaluation will be scheduled on the date of deferral. Postoperative infection should be mitigated as early as possible, given the higher risk of mortality during postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%